Research Brief #18: Food prices, their determinants and connections to child nutrition in Nepal. - Shively, Gerald; Thapa, Ganesh. (Tufts University. Tisch Library., 2016)
This briefing dives into the links between food prices and child nutrition in Nepal. District and regional details are explored. Keywords: Nutrition Innovation Lab, Research Brief, PoSHAN (Policy and Science for Health, Agriculture and Nutrition), Suaahara.; Feed the Future Innovation Lab for Nutrition, USAID Contract No. AID-OAA-L-10-000006, managed by Tufts University's Gerald J. & Dorothy R. Friedman School of Nutrition Science and Policy